The influence of project characteristics on contractual behaviour of key participants in civil engineering projects / Wan Norizan Wan Ismail and Hamimah Adnan - Wan Ismail, Wan Norizan; Adnan, Hamimah (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
This paper described the importance of paying attention on the aspects of project characteristics in understanding the contractual behavior of key participants in civil engineering projects. The purpose of this paper was to identify the project characteristics variables contributing to the unfavorable contractual behavior of key participants in civil engineering projects. An extensive literature review was carried out using content analysis and unveiled nine (9) civil engineering project characteristics that may contribute to the contractual behavior of key participants. They were project type, project size, project scope changes, design changes, site surrounding condition, ground condition, project complexity, procurement method, type of standard form of contract. The findings provide basis for understanding the factor that influence the contractual behavior of key participants in order to comprehend the constraints faced by them in implementing the civil engineering projects. Hence, the initiatives or proactive preventing actions can be suggested in future study to improve the contractual behavior of key participants and eventually will lead to the project success.